TRADITIONS AND INNOVATIONS IN MUSIC LITERATURE LESSONS - Ildarova Nadezhda Sergeevna (American Journals Publishing, 2026)
This article explores how to balance traditions (close listening, contextual reading, stylistic comparison, and culturally grounded interpretation) with innovations (streaming archives, interactive media, flipped learning, multimodal projects, and learning analytics) so that technology extends musical thinking rather than replacing it.
Keywords: Music literature, guided listening, digital pedagogy, blended learning.